Implementation Of The Digital Economy In Matano Tourism Village - Adrian Polim; Sutrisno K.Djawa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Every Indonesian region has the potential to profit from the tourism industry, particularly with the help of information technology advancements. In actuality, though, a large portion of Indonesian tourism has not completely embraced digitalization to its full potential. similar to Matano Village in East Luwu Regency, which struggles to combine efficient marketing with administration. The objective of this study is to enhance the tourism industry in Matano Tourism Village by utilizing the Digital System Enterprise Resource Planning. The goals of this makeover are to improve awareness, draw in more visitors, and make managing tourist villages easier. To thoroughly evaluate the state of tourism in Matano Village, a qualitative and descriptive research methodology was applied. Primary data was gathered using gform surveys, in-person observations in Matano Village, and interviews with specific populations. Journals, literature, and documentation are sources of secondary data. There is also the waterfall method. The results of the research show that integration is still restricted and that Matano Village's tourism potential has not been fully realized.